Mündliche Handlungsfähigkeit des Deutschlehrers - Umrisse eines Forschugsprojekts - RICHTER, Günther (Uniwersytet im. Adama Mickiewicza, 1995)
The paper refers to the basic problems of the oral management of the classroom, mainly in the case of the German language teaching process. It defines the most essential notions connected with this subject and puts forward a sequence of hypotheses answering the most important questions, e.g. behavioral norms and patterns of the teacher, along with a number of methodological instructions.